On Filtration in a Rectangular Interchange with a particularly Unpermatable Vertical wall in the Evaporation - E.N., Bireslavskii; L.M., Dudina (Journal of Water, 2018)
We consider a plane steady-state filtration in a rectangular bridge with a partially impermeable vertical wall in the presence of evaporation from a free surface of groundwater. To study the effect of evaporation, a mixed multiparametric boundary-value problem of the theory of analytic functions is formulated and using the method of P. Y. Polubarinova-Kochina. Based on the proposed model, an algorithm is developed to calculate the dependence of efficiency and productivity of hydrodynamic analysis.
Keywords: filtration; evaporation; jumper; ground water; free surface; Polubarinova-Kochina method; complex velocity; conformal mappings; differential equations of the Fuchs class.